(untitled) (Annals of Medical Research, 2021)
Aim: Due to anatomical differences, current baseplate designs may lead to incompatibilities in reverse shoulder arthroplasty in different populations. We hypothesized that glenoid anthropometric parameters in Turkish subjects would be different from that in other populations.Material and Methods: Three-dimensional morphology of 200 healthy Turkish shoulders (100 male and 100 females, 93 left and 107 right shoulders) was evaluated. Glenoid height, width, version, inclination, circumference, and surface area; glenoid depth, scapular neck length, and scapular neck angle were measured. Sex and side differences were assessed. The correlation between glenoid morphologic parameters and subject height was assessed. The height corresponding to a 25-mm glenoid width was predicted.Results: There was a significant difference between male and female subjects regarding glenoid height, width, version, depth, circumference, surface area, and patient height (p0.05). Also, there was a significant difference between right and left shoulders regarding glenoid height, glenoid width, glenoid version, glenoid surface area, superior depth, central depth, and inferior depth measurements (p0.05). The glenoid height, width, retroversion, depth, circumference and surface area was well correlated with subject height. The estimated body height value to be obtained for a 25 mm glenoid width value was calculated as 164.4 cm.Conclusion: Our results would be useful in patient selection, preoperative planning, determining the appropriate glenosphere sizes and glenoid component placement. The values of measurement parameters in this study may serve as reference values for normal Turkish population and may be helpful in the comparisons with other populations and osteoarthritic glenoids.